Construction of the concept of ratio and constant ratio from the social epistemological viewpoint - Espinosa Romero, César Iván; Jiménez Espinosa, Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article describes, based on detailed classroom interactions, how some social practices of knowledge construction go with the basis of the concept of ratio and constant ratio as a previous phase to its own formalization. This is the result of a research, whose objective was to characterize the process of the social and the contextual knowledge construction that a group of students carries out, related to the concept of derivative at a point, from the social practices (as explained by the social epistemology) and the classroom interactions. This research had its basis on the social epistemology, which criticizes the theoretical mathematical school discourse, and considers that knowledge emerges from situated social practices. The methodological scheme of the social epistemology and the content analysis were used here. The reason of this research is the fact that the theoretical school discourse does not make up propitious basis for math learning, according to social epistemologists. The results give way to the conclusion that some simulation practices make such knowledge construction possible. At the end of this article the practices are stated and the construction is described.